Nghiên cứu cơ chế của quá trình peroxydasa trong hệ H2O-Ni2+-HCO3--Lm-H2O2 (1) - Kim Loan, Vũ Thị (Vietnam Journal of Chemistry, 2016)
By using method of using inhibitor, it was found that the catalytic process of indigocarmine (Ind) oxidation take place according to the radical chain mechanism with a generation of free active OH* radical reacting with Ind, H4L, In (Lumomagnezone  - Lm, Hydroquinon - Hq, Paranitrozodimetylanilin - Pa) in the systems: H2O - Ni2+ - HCO3- - Lm - Ac -H2O2 (2) H2O - Ni2+ - HCO3- - Lm  - Hq -H2O2 (3) H2O - Ni2+ - HCO3- - Lm - Pa -H2O2 (4) This article presents our results of calculating the rate constant k(Ind+OH*) of oxidizing reaction of Indigocarmine by hydroxyl radicals OH*. k(Ind + OH*) was calculated by using Turbopascal programming languages. Keywords. Inhibitor, indigocarmine, hydroxyl radicals.